Homilie Rabana Maura na niedzielę, dni nabożeństw błagalnych oraz o świętych (wybór) - Łukaszczyk, Michał (Vox Patrum, 2022)
The work consists of two parts. In the introduction, I provided a short presentation of Rabanus Maurus’ biography. Next, I presented a short description of his homilies, while taking into account the tradition and the epochal context. In the last part of the introduction, I provided a short description of homilies which I have translated. In the homilies themselves, the author takes up the following themes: fidelity to the principles of the Christian religion, warning against giving in to pagan influences, explanation of the most important truths of the faith, reinforcing one’s own preaching by providing ample quotations from Sacred Scripture as well as making use of the Church Fathers’ writings. In his homilies, Rabanus Maurus takes up other themes as well, such as: warning against hunting and playing dice on holy days, forbidding conversations in church and work on holy days and requesting care for the poor and the blind. These issues which seems to be less important had a significant importance for the author’s contemporaries. In the annotations, I included the most important philological, theological, biographical and geographical observations which allow the reader to properly understand the context of the translated homilies.